Tongue Picture is considered as a novel and non-invasive earlier diagnosis than ever for esophagus cancer - Li, Xinhui (JOURNAL OF ADVANCES IN BIOLOGY, 2016)
The invasive, unpleasant and inconvenient nature of current diagnostic about esophagus cancer limits their application in clinical practice. There is a great need of novel non-invasive method for early esophagus cancer diagnosis. In the present study, we intend to determine whether the tongue pictures are suitable for early detection of esophagus cancer.